IMAGE AND SYMBOL OF A FLOWERING WOOD IN ART OF CHINA AND EUROPE - Лай, Юеге (Art and Design, 2019)
The purpose of the study is to reveal the figurative and symbolic parallels of the image of a flowering tree in the art of China and Europe. When studying the topic chosen by us, it was especially important to use a comparative method, which allows comparing works of art from Europe and China based on related subjects from different time periods and identifying the general and the particular. The artistic-stylistic and iconological method is actively used. Iconology along with the iconography allows to perceive the symbolic content of the work. It has been established that the image and symbol of a flowering tree is one of the most important in the art of China and Europe, since it expresses the idea of the eternal revival of nature and the person associated with it. Unlike the art of Europe, where people are in the center of attention, the genre of “Flowers and Birds” and the landscape “Mountains – Waters” dominate in China. European artists of the second half of the 19th and early 20th centuries came closest to the art of the Far East. Over time, nature in the art of Europe became an independent genre, the image of a flowering tree comes to the fore in relation to the image of a man. In times of crisis in nature sought harmony. In the striving of European artists to get away from direct, realistic reproduction of the landscape and create a mediated, conditional symbolic landscape, the aspiration of the masters of the new directions of the XIX – XX centuries to the poetics of beauty, to the expressiveness of line and color influences. The culture of the Far East helped to go beyond the anthropomorphic mythology of the Mediterranean culture of Europe; enrich figurative and symbolic content; artistic facilities; artistic and stylistic opportunities; change and expand the genre boundaries of art. Scientific novelty of the publication lies in the fact that it was the first time when it compared the image and symbol of a flowering tree in the art of China and Europe.